Laparoscopic Management of Ureteral Calculi: A Report of 123 Cases - Simforoosh, Nasser; Basiri, Abbas; Danesh, Abdolkarim; Ziaee, Seyed Amir Mohsen; Sharifiaghdas, Farzaneh; Tabibi, Ali; Abdi, Hamidreza; Farrokhi, Farhat (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0; @font-face font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: Our aim was to evaluate the efficacy and safety of laparoscopic surgery for the management of ureteral calculi. Materials and Methods: We performed 123 laparoscopic calculus removal in 103 men and 31 women. Indications for the procedure were extracorporeal shockwave lithotripsy or transureteral lithotomy failure and large calculus. The mean age of the patients was 39.6 Â± 13.8 years. The calculi were between 1 and 5.6 cm and located in the upper, middle, and lower ureter in 90 (73.2%), 20 (16.3%), and 13 (10.5%) patients, respectively. Ureteral stent was used in 52 (42.3%) patients. We used 3 ports for camera and instruments. Intraperitoneal approach was used in 104 (84.6%) and extraperitoneal in 19 (15.4%). Results: The mean operative time was 143.2 Â± 60.5 minutes. One hundred and nineteen patients (96.7%) became stone free. Minor complications occurred in 14 (11.4%) patients. Conversion to open surgery was required in 1 patient due to migration of the calculus to the peritoneum after removal from the ureter. Intra-abdominal hematoma led to reoperation 1 day after the surgery in 1 patient. Operative time was different significantly between extraperitoneal and intraperitoneal approaches (171.3 Â± 91.3 minutes and 137.3 Â± 52.2 minutes, respectively; P = .02). Conclusion: Our results confirm the efficacy and safety of laparoscopic removal of ureteral calculi in selected groups of patients, taking the advantage of this minimally invasive procedure such as better cosmetic results and patientâ€™s satisfaction.